Secrets of the Forbidden City - Bremner, Ian; Meyers, Eric, 1959-; Lion Television Ltd.; WGBH (Television station : Boston, Mass.); Channel Four (Great Britain); ARTE France; China Intercontinental Communication Center; Public Broadcasting Service (U.S.); PBS Distribution (Firm) (Alexandria, Virginia PBS, 2017)
In a laboratory, a team of engineers create a replica of Beijing's Forbidden City to uncover the secrets underlying its ability to withstand earthquakes over the centuries.
Documentary.
Originally produced as an episode of the television series: Nova.
Program content: 2017.
Widescreen presentation.
Running time indicated on container: approximately 60 minutes; actual running time: 54 minutes.
Narrator, Eric Meyers.
Keywords: Forbidden City (Beijing, China) -- Buildings, structures, etc. -- Design and construction; Forbidden City (Beijing, China); Earthquake resistant design -- China -- Beijing -- History; Earthquake engineering -- China -- Beijing -- History; Palaces -- China -- Beijing -- Design and construction -- History; Palaces; Beijing (China) -- Buildings, structures, etc. -- Design and construction -- History; China -- Beijing; Documentary television programs; Science television programs; Nonfiction television programs; Video recordings for the hearing impaired; History